ВИВЧЕННЯ КОЛОРИСТИЧНОЇ КУЛЬТУРИ СТАРОДАВНЬОГО ЄГИПТУ УЧНЯМИ ПОЧАТКОВОЇ ШКОЛИ АНОТАЦІЇ (Педагогіка вищої та середньої школи, 2008)
In the article «Study of color istical culture of Ancient Egypt of pupils at secondary school» gives her point of view about the substantial aspects of use the interesting facts about the coloristical culture of Ancient Egypt on the lessons offine art, method of study of this culture at secondary school.